STUDI DISORDER LAPISAN TIPIS AMORF SILIKON KARBON (a-SiC:H) HASIL DEPOSISI METODE DC SPUTTERING - Munisa, Lusitra; Saleh, Rosari (UI Scholars Hub, 2002)
Disorder Study of Amorphous Silicon Carbon (a-SiC:H) Films Deposited by DC Sputtering Method. Disorder amorphous network of amorphous silicon carbon (a-SiC:H) films has been investigated for films prepared by dc sputtering method. The films were deposited using silicon target in argon and methane gas mixtures. The optical absorption coefficients have been performed by UV-VIS (ultra violet-visible) reflectance and transmittance spectroscopy. Disorder parameter has been obtained from the optical absorption coefficient α (E) using Tauc plot. Increasing methane flow rate has an effect on increasing Tauc gap and decreasing disorder parameter. The amorphous network of the films tends to be more disorder with increasing methane flow rate. The relation of disorder amorphous network with structural and compositional properties will be discussed.